Les contentieux du travail en droit anglais - Slynn, Sir Gordon (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
In this article, the author describes the British system of Labour Tribunals. These Tribunals, which are composed of jurists and non-jurists have jurisdiction to hear claims dealing with unlawful dismissal, discriminatory practices and other such matters. Although the workload is impressive, there is easy access to the Tribunals and a flexible procedure is used. An appeal on questions of law is provided for from those Tribunals to the Employment Appeal Tribunal, which is composed of one judge and two non-jurists. The author has acted as chairman of the Employment Appeal Tribunal and is clearly in favor of such a mixed composition. The article describes the decision-making process of the Appeal Tribunal and its powers.